Effects of ABO blood groups and RH-factor on COVID-19 transmission, course and outcome: A review - Abuawwad, Mohammad T.; Taha, Mohammad J. J.; Abu-Ismail, Luai; Alrubasy, Warda A.; Sameer, Shams Khalid; Abuawwad, Ibrahim T.; Al-Bustanji, Yaqeen; Nashwan, Abdulqadir J. (Frontiers in Medicine, 2023)
The ABO and Rh blood grouping systems are two of the non-modifiable risk factors that play an important role in the susceptibility, severity, and outcomes of COVID-19 infection. A link has been drawn between blood groups and COVID-19 transmission, course, and prognosis, as the literature suggests that blood group O plays a protective role against the infection while blood group A exhibits a higher risk of exacerbation. In contrast with Rh-negative individuals, Rh-positive individuals are prone to more severe infections and complications, despite the fact that the underlying mechanisms of this association remain understudied. Nevertheless, the connection remains subject to controversy since some studies report doubts about it. Thus, this association requires further investigation. This review explores these associations all over the world in an attempt to conclude a clear idea for future reference in clinical practice.